CROSS- CULTURAL ENTITLEMENT AND RESILIENCE: A SUGGESTION FOR WESTERN COGNITIVE THERAPY - Spyropoulos, Daphne Catherine (PEOPLE: International Journal of Social Sciences, 2018)
The focus of this review is to qualitatively research the cross- national dissonance between psychiatric findings suggesting that affluent countries of the West suffer a greater prevalence of depressive and anxiety disorders as compared to countries of the Developing world that are proven more resilient. The author of the paper has aggregated the multiple definitions of resilience, has detected examples of its disparity across different countries and has analyzed cognitions of the developing world that are reinforcing it, differences in cognition between the Developing and the Western world as well as a sense of entitlement and other cognitions of the Western world that counteract it. Through a parallel analysis of entitlement - based cognitions of the Western world and of adaptive cognitions of the Developing world, the author suggests a resilience- promoting cognitive therapy route, in which the latter can act as superior alternatives to the former.